2017
DOI: 10.21511/imfi.14(4).2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Corporate governance quality, firm size and earnings management: empirical study in Indonesia Stock Exchange

Abstract: Earnings management (EM) is manipulation done by management in preparing financial statement in order to gain management advantages or to increase the firm value. EM can reduce the quality of financial statements because it does not show the real earning periodical. This research aims to identify the effect of good corporate governance (GCG) (institutional ownership, managerial ownership, frequency of board meetings, frequency of audit committee (AC) meetings), firm size, and leverage on the EM. Population com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0
23

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 10 publications
8
33
0
23
Order By: Relevance
“…On the other hand, INSOWN have significant and positive impact on EM which shows that if INSOWN increase, EM will be increased accordingly, (It reflect that the institutional ownership have negative and significant impact on FRQ), these results supported by Koh [59], Adebiyi, and Olowookere [37], Affan et al [11]. Also; the results indicate that MAOWN have insignificant impact on EM, and these results on the same line with Agustia [60], Saftiana et al [43]; Affan et al [11]. The finding of this equation supported the three hypotheses that BDOWN, FMOWN, INSOWN have significant impact on EM.…”
Section: B Measurement the Variablessupporting
confidence: 56%
See 1 more Smart Citation
“…On the other hand, INSOWN have significant and positive impact on EM which shows that if INSOWN increase, EM will be increased accordingly, (It reflect that the institutional ownership have negative and significant impact on FRQ), these results supported by Koh [59], Adebiyi, and Olowookere [37], Affan et al [11]. Also; the results indicate that MAOWN have insignificant impact on EM, and these results on the same line with Agustia [60], Saftiana et al [43]; Affan et al [11]. The finding of this equation supported the three hypotheses that BDOWN, FMOWN, INSOWN have significant impact on EM.…”
Section: B Measurement the Variablessupporting
confidence: 56%
“…Teshima & Shuto [41], Han [42], Apriada & Suardikha [31] revealed that weak supervision of high managerial ownership levels can reduce the FRQ. Saftiana et al [43] and Affan [11] found that managerial ownership does not has significant impact on EM or FRQ.…”
Section: E Managerial Ownership and Financial Reporting Qualitymentioning
confidence: 99%
“…Penelitian ini tidak sejalan dengan teori agensi yang menyatakan bahwa dewan komisaris yang bertugas sebagai principal dapat mempertanggungjawabkan segala tugasnya dalam meningkatkan kinerja perusahaan dalam mengurangi tindakan manajemen laba. Hasil penelitian ini mendukung penelitian Prastiti dan Meiranto (2013) dan Saftiana et al (2017) yang menemukan bahwa frekuensi pertemuan dewan komisaris tidak berpengaruh signifikan terhadap manajemen laba.…”
Section: Pengujian Hipotesis 3 Jurnal Akuntansi Syariahunclassified
“…Menurut Prastiti dan Meiranto (2013) komite audit tidak melaksanakan tugas dan tanggung jawabnya secara maksimal sehingga fungsi dan perannya untuk mengawasi manajemen tidak efektif. Menurut Saftiana et al (2017) terkadang anggota komite audit tidak memiliki latar belakang pendidikan akuntansi atau keuangan, dimana hal ini bisa menjadi alasan manajemen untuk dapat memanipulasi laporan keuangan. Penelitian ini juga tidak sejalan dengan teori keagenan yang menyatakan bahwa dewan yang independen selalu memberikan pengawasan yang efektif terhadap manajemen dimana dengan adanya independensi yang baik akan semakin lengkap dan efektif dengan adanya keaktifan komite audit dalam mengadakan pertemuan.…”
Section: Pengujian Hipotesisunclassified
See 1 more Smart Citation